Radiata pine response to tillage, fertilization, and weed control in Chile - ALBAUGH,TIMOTHY J (Universidad Austral de Chile, Facultad de Ciencias Forestales, 2004)
Four radiata pine (Pinus radiata) stands were established on recent volcanic ash, volcanic sands, old volcanic ash and fluvial sedimentation in a granitic zone in Chile in 2000. Weed control (none or two year banded), fertilization (1.5 g B per tree or 150 g diammonium phosphate+1.5 g B per tree), soil tillage (shovel or subsoil), and all combinations of the individual treatments were applied with four replications at each site and analyzed as a split plot design with soil tillage as the main plots and weed control and fertilization as the sub plots. Treated plot area was at least 0.4 ha with 10 m buffers between all plots. Height, root collar diameter and diameter at breast height were measured three years after planting and foliar nutrient concentrations were measured two years after planting. All four sites exhibited positive growth responses to weed control with an average response to weed control across all sites of 3.1 cm in diameter and 1 m in height after three years. A positive height response (10 cm) to fertilization was observed on the volcanic sands. However, foliar nutrient analysis indicated that the added fertilizers may not have been available to the crop trees due to the timing of application. Subsoil tillage improved growth on the volcanic sand and the fluvial sedimentation sites, however the magnitude of response was 95% and 42% less than the response to weed control on these same sites, respectively. Weed control and subsoil tillage reduced variability in height at all sites. We hypothesized that early rotation growth gain from weed control would be maintained throughout the rotation (Type B) on old volcanic ash and the fluvial sedimentation sites while the growth gain on the recent volcanic ash and the volcanic sand sites would be partially or completely lost by the end of the rotation (Type C). Certainly, weed control is recommended for the site types represented in these trials. Fertilization along with weed control is recommended on the volcanic sands. Additional study managing the timing of fertilizer application is indicated as the applied fertilizers may not have been available to the crop trees. Subsoil tillage may not be needed on these site types however secondary benefits like improved traffic-ability and ease in planting resulting from subsoil tillage need to be quantified to better evaluate subsoil tillage benefits.